2013
DOI: 10.1103/physreva.87.042310
|View full text |Cite
|
Sign up to set email alerts
|

Time evolution of tripartite quantum discord and entanglement under local and nonlocal random telegraph noise

Abstract: Few studies explored the dynamics of nonclassical correlations besides entanglement in open multipartite\ud quantum systems. Here, we address the time evolution of quantum discord and entanglement in a model of\ud three noninteracting qubits subject to a classical random telegraph noise in common and separated environments.\ud Two initial entangled states of the system are examined, namely the GHZ- and W-type states. The dynamics\ud of quantum correlations results to be strongly affected by the input configura… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
31
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 51 publications
(145 reference statements)
7
31
2
Order By: Relevance
“…Where N  is an N×N identity matrix. As expected according to the definition of an entanglement witness operator given above, negative expectation values of the entanglement witnesses GHZ N  ( ) and W N  ( ) indicate the appearance of multi-qubit entanglement experimentally detectable in the system meanwhile zero or positive expectation values do not guarantee the absence of entanglement [58].…”
Section: N-qubit Entanglement Witnessesmentioning
confidence: 52%
See 2 more Smart Citations
“…Where N  is an N×N identity matrix. As expected according to the definition of an entanglement witness operator given above, negative expectation values of the entanglement witnesses GHZ N  ( ) and W N  ( ) indicate the appearance of multi-qubit entanglement experimentally detectable in the system meanwhile zero or positive expectation values do not guarantee the absence of entanglement [58].…”
Section: N-qubit Entanglement Witnessesmentioning
confidence: 52%
“…For instance, it has been found that for multi-qubit systems, the degree of entanglement robustness tends to increases or decreases with the increase of the number of qubits of the system [8,56]. In particular, the dynamics of quantum correlations in terms of entanglement and discord in a physical model of three non-interacting qubits subject to a classical environmental noise has recently been investigated [57][58][59]. In the present work, in order to have an insight on how the entanglement behaves in the model studied in the above mentioned works (that is, [57][58][59]) when the number of qubits is increased, we extend this model from three to four qubits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This system is the bosonic version of the Hubbard plaquette, which is used in solid state as a building block for highly correlated manybody systems [108][109][110][111]. In agreement with previous works [61,66,67,90], in order to mimic the effect of the noise on the quantum system the hopping amplitudes among the sites are assumed to follow a time-dependent stochastic behavior. Such an assumption yields the Hamiltonian [27,40] …”
Section: Two-boson Bose-hubbard Modelmentioning
confidence: 98%
“…Campbell et al used fidelity-and collective-spin-based entanglement witnesses to analyze the dynamics of genuine multipartite entanglement of Dicke states under local amplitude-damping, phase-damping, and depolarizing channels [46]. Tripartite negativity and generalized concurrence were also applied to the dissipative dynamics of GHZ and W three-qubit entangled states [47][48][49][50][51][52]. Let us recall that the above measures are not precise, i.e., their zero values do not imply in general that the genuine entanglement is lost.…”
Section: Introductionmentioning
confidence: 99%